Elementary School Guidance in Canadian Urban Areas: A Study of Present Counsellor Functions - Merchant, Dave; Zingle, Harvey W. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of the study was to clarify the status of elementary schoolguidance in Canadian urban areas. Information on the counsellor's background and the counsellor's work setting were obtained from the responses on the Counsellor Data Blank which was developed by the authors and the 100-item Guidance Services Opinionnaire, a modified version of the Raines Opinionnaire, which was used to determine what the counsellor was presently doing in the school. Results on counsellor characteristics indicated that the typical counsellor had some limited guidance training — either a guidance diploma or was in the process of completing such requirements. The counsellor had at least two years teaching experience and his professional affiliation was usually with the local or provincial association. Many counsellors were faced with large counsellor-pupilratios. Most of the guidance programs were begun in the late 1960's. In terms of present activities counsellors focused their energies on individual contacts concerning children with learning or adjustment difficulties. The results were also examined in terms of Developmental and Traditional approaches to elementary school guidance. The results indicated that counsellors were frequently involved with the traditional activities.